Xerostomia in primary care: a register-based study of prevalence, medication categories, and associated risk factors - Rughwani, Vini; Miao Jonasson, Junmei; Marklund, Bertil; Mossberg, Karin; Almståhl, Annica; Lynge Pedersen, Anne Marie; Cevik-Aras, Hülya (Frontiers in Oral Health, 2025)
ObjectivesXerostomia, the subjective sensation of oral dryness, is often associated with reduced salivary secretion. Xerostomia is a prevalent side effect to numerous medications but also found associated with aging and female sex. The objective of the study is to estimate the prevalence of xerostomia in association with the number and type of medications used by adults in the region of Västra Götaland, Sweden.Materials and methodsData on age, sex, and medication use in patients diagnosed with xerostomia, using International Classification of Disease (ICD) 10 code 11.7 and R68.2 was obtained from the health care database in the region of Västra Götaland, Sweden (Vega). Prevalence of xerostomia diagnosis was estimated according to the type and number of medications consumed, stratified by age and sex.ResultsThe overall prevalence of xerostomia diagnosis was 0.23%. Medication was strongly associated with xerostomia, with the highest percentage of diagnosis observed in patients taking medications for treatment of metabolic diseases and diseases in alimentary tract (16.07%), the nervous system (16.04%), and the cardiovascular system (12.63%). Xerostomia was also associated with the number of medications. Polypharmacy (concomitant intake of five or more medications) and aged over 71 years was associated with 9.68-times higher odds for xerostomia (p < 0.0001). Females were more likely to be diagnosed with xerostomia, representing 73.08% of cases compared to 26.92% for males (p < 0.0001). The prevalence of xerostomia was lowest in the 18–35 age group (9.56%) and highest in those aged above 71 years (41.49%). Patients aged 55 years and older were significantly more likely to be diagnosed with xerostomia than younger patients (p < 0.0001).ConclusionsThe findings emphasize a strong association between medication use, particularly polypharmacy, and xerostomia, with substantial variations across age, sex, and medication categories. Despite the high risk, a low prevalence of xerostomia diagnosis was reported in primary care settings. The findings suggest a need for increased clinical awareness and routine assessment to improve detection and management.